IDENTIFY THE RESPIRATION SYSTEM AND THE ORGANTS OF THEM - Rini Mahmud (Jurnal Ilmiah dr. Aloei Saboe, 2022)
Respiration is the process of exchanging gases between organisms and their environment. Respiration involves taking in oxygen, circulating it to cells, and releasing carbon dioxide. The process of respiration involves the respiration medium, the respiratory membrane, and the respiratory organs. Respiration function to maintain pH balance and electrical balance in body fluids. Gas diffusion between the respiratory organs and the environment can occur due to differences in gas pressure. The purpose of this research is to know the anatomy of the respiratory system and to know the function of the respiratory system and its constituent organs. The method used is the experimental method, the experimental method is an experiment to prove a certain question or hypothesis. Experiments can be carried out in a laboratory or outside the laboratory, experimental work means learning to do, because it can be included in the learning method. The objectives of the experimental method: 1) students are able to conclude the facts, information or data obtained; 2) students are able to design, prepare, implement and report research results. The results showed that the lung capacity volumes of the two groups of different sexes. probandus one (male). with a body weight of 51.1 kg, height 168 cm and chest circumference at inspiration 88 cm and 87 cm at the time of expiration, lung capacity 2.13 ml. Probandus two (female) weighing 43.6 kg, height 145 cm and chest circumference at inspiration of 83 cm and 79 cm on expiration, lung capacity 1.13 ml. The lung capacity of men is greater than that of women, because men are generally more active than women, so the volume of the lung capacity of men is large and requires a large amount of oxygen.